Detrital zircon (U–Th)/He thermochronometry of the Mesozoic Daba Shan Foreland Basin, central China: Evidence for timing of post-orogenic denudation - Tian, Y.; Qiu, N.; Kohn, B.; Zhu, C.; Hu, S.; Gleadow, A.; McInnes, Brent (Elsevier Science BV, 2012)
The timing of the transition of a peripheral foreland basin from underfilled to overfilled provides important insights into the post-orogenic dynamics of its coupled orogenic wedge. Such information is lacking in the Mesozoic foreland basins surrounding the Qinling Orogen, central China, such as the Daba Shan Foreland Basin (DSFB), the northeastern part of the Sichuan Basin. In an effort to constrain the timing of maximum burial and onset of denudation, we report detrital zircon (U–Th)/He (ZHe) data from four deep boreholes in the DSFB. Results show that ZHe ages from the oldest foreland basin formations (Upper Triassic–lower Middle Jurassic) are mostly younger than their depositional age, whereas non-reset ZHe ages characterize younger strata. This suggests that the oldest strata attained maximum temperatures between ~130 °C and 200 °C (ZHe partial retention zone), which is consistent with previous independent paleotemperatures (organic matter reflectance and illite crystallinity) reported in two of the boreholes and another nearby.The fully reset ages apparently show the youngest peaks at ~80 Ma and ~100 Ma, which are interpreted as the minimum constraints on the timing of maximum basinal burial and subsequent denudation. Considering that the regional deposition has lasted to Aptian time, it is proposed that the onset of the basin exhumation in the DSFB started at Aptian–Albian time (~100–125 Ma), heralding the termination of regional tectonic shortening in the hinterland (Southern Qinling).